Solution.
1.
"y(3x^3-x+y)dx+x^2(1-x^2)dy=0"This is the first order nonlinear ordinary differential equation.
Divide on "x^2(1-x^2)dx."
"y'-\\frac{3x^2-1}{x^3-x}y=\\frac{y^2}{x^4-x^2}."
We have Bernuli's equation for n=2.
Divide by "y^2."
Replacement "u=\\frac{1}{y}," then "u'=-\\frac{y'}{y^2}, y'=-u'y^2."
"u'+(\\frac{3x}{(x-1)(x+1)}-\\frac{1}{x(x-1)(x+1)})u=-\\frac{1}{x^4-x^2}"
This is the first order linear equation.
Let be "P(x)=\\frac{3x}{(x-1)(x+1)}-\\frac{1}{x(x-1)(x+1)}."
"\\int P(x)dx=\\int \\frac{3x}{(x-1)(x+1)}-\\frac{1}{x(x-1)(x+1)}dx=\\ln (x^3-x)+C,"
where C is some constant.
Solve
"u'+P(x)u=0,""\\frac{du}{u}=-P(x)dx,"
"\\int\\frac{du}{u}=-\\int P(x)dx,"
"\\ln u =\\ln (x^3-x)+C,"
"u=\\frac{C}{x^3-x}."
The solution of "u'+(\\frac{3x}{(x-1)(x+1)}-\\frac{1}{x(x-1)(x+1)})u=-\\frac{1}{x^4-x^2}" find by the method of variation constant in the form "u=\\frac{C(x)}{x^3-x}."
Thus "u=\\frac{-\\ln x+C}{x^3-x}."
From here "y=\\frac{x-x^3}{\\ln x+C}."
Answer. "y=\\frac{x-x^3}{\\ln x+C}."
2.
This is the first order nonlinear ordinary differential equation.
Replacement "y=\\sqrt{z}," then "dy=\\frac{dz}{2\\sqrt{z}}." We will have
Replacement "u=\\frac{z}{x}," then
"x=ux, dz=udx+xdu."
We will have
"(\\frac{\\sqrt {u}x^{5\/2}}{2}-\\frac{x^{5\/2}}{2\\sqrt u})du=(-\\frac{3u^{3\/2}x^{3\/2}}{2}-\\frac{3\\sqrt u u^{3\/2}}{2})dx."
Divide by "x^{5\/2}" and "-\\frac{3u^{3\/2}x^{3\/2}}{2}-\\frac{3\\sqrt u u^{3\/2}}{2}."
We will have
"\\int(\\frac{1}{3u(u+1)}-\\frac{1}{3(u+1)})du=\\int\\frac{dx}{x}."
"\\frac{\\ln u}{3}-\\frac{2\\ln (u+1)}{3}=\\ln x+C,"
where C is some constant.
From here
Thus
So we have answer
Answer. "y^2=Cx^2(y^2+x)^2."
Comments
Leave a comment